The ability of the natural chemoprophylactic agent curcumin to function as an effective UV photosensitiser - Potapovich, Alla I.; Shutava, Tatsiana G.; Kostyuk, Tatyana V.; Kostyuk, Vladimir A. (Experimental Biology and Biotechnology, 2021)
It is known that some plant polyphenols and alkaloids can act as effective photosensitisers of UV radiation. This phenomenon can enhance both therapeutic and side effects. Since there is no information regarding curcuminoids on their ability to function as UV photosensitisers, this work investigated the effect of UV radiation on the cytotoxic effect of curcumin, as well as its nanostructured forms, against keratinocytes of the HaCaT line and cancer cells MDA-MB-231. The results obtained indicate that curcumin is an effective photosensitiser capable of initiating photochemical reactions under the influence of UV radiation of the A and B range, which lead to the formation of chemically active intermediates, disruption of membrane integrity and cell death. When curcumin is incorporated into nanostructures based on polyallylamine hydrochloride /polystyrene sulfate and chitosan /dextran sulfate, its ability to function as a UV photosensitiser is retained.